The implementation of a toy-based program for children to enhance their problem-solving skills in the Philippine toy library - Pascua, Vinny Andrew B. (2016)
This research sought to determine whether toy-based programs can improve the problem-solving skills of children. The experimental study was conducted at the Philippine Toy Library at Loyola Heights, Quezon City. Five preschoolers underwent a toy-based program which aims to enhance their logic reasoning, memory, and creativity. It ran for five weeks. There were two sessions per week and each session lasted for 30 minutes. A pretest and post-test was done to measure any development. The researcher also conducted a survey to know the perception of the respondents and actual children visitors towards the Philippine Toy Library and their insights on the implementation of toy-based programs.